Impact of Macroeconomic Determinants on Stock Market Performance in Nepal: A Vector Error Correction Model Analysis - Thapa, Krishna Bahadur; Kunwar, Prashmasha (KIC International Journal of Social Science and Management, 2024)
This study explores the long-term and short-term relationships between the Nepal Stock Exchange (NEPSE) and key macroeconomic variables, including liquidity, reserve money, the Consumer Price Index (CPI), and foreign exchange rates. It employs the Vector Error Correction Model (VECM) with the time series data. The study aims to explore how these macroeconomic factors influence, to examine the long run relationship, and assess the causal direction on the stock market movements in Nepal. The Johansen Cointegration Test reveals a long-term equilibrium relationship between these variables. The reserve money and foreign exchange rates show positive effects on NEPSE, while CPI and liquidity exhibit negative impacts. Specifically, reserve money and foreign exchange rates have a significant positive correlation with NEPSE. Conversely, higher CPI and increased liquidity are found to negatively affect the stock market in the long-run. The Granger Causality Test indicates that reserve money and foreign exchange rates Granger cause NEPSE, while the stock market itself Granger causes consumer price index.